Use of Online Social Networking Services in University Libraries: A Study of University Libraries of Karnataka, India - Tadasad, Prahalad G; K, Deepthi; Patil, Shobha (DESIDOC Journal of Library & Information Technology, 2017)
Social networking services have become a very powerful tool to provide library services. Over a period of time libraries are using online social networking services to make their services popular and user friendly. Social networking services like facebook, youtube, twitter, linkedin, google+, instagram have many applications that could be utilised by the libraries to provide number of services in libraries. The paper reports the use of social networking services in University libraries, based on a study of 54 university websites in Karnataka state. Method of content analysis has been adopted to study the websites. The results indicate that 53 of 54 universities (98.14%) do have their own websites in different domains. 29.62% State/Central universities are connected to Facebook. 18.51% are connected to Youtube. Very few are connected to Twitter and Linkedin. 18.51% of Universities are connected to different networking sites. It is observed that the universities libraries in the state are catching up with these technologies but many of these services are used for mere elementary purposes. The study concludes that it is time for the university libraries to exploit the services and use the optimum potentialities of these Social networking services.